MALE FACTOR - Tejada, Alberto (2015)
About 8 to 15% of the world copules suffer fertility problems and in about 40% the male factor interferes. Today, thanks to the scientific advances we can elaborate better diagnosis, treatments and improve the reproductive quality in an important number of cases and bring about the longed fertility to the couple.